Bakar Babi: Dari Ritual Budaya ke Simbol Politik Suku Moskona dalam Pemilihan Legislatif di Teluk Bintuni, Papua Barat - Wahid, Bustamin; Mardliyah, Uswatul; Ula, Siti Nurul Nikmatul; Purwanti, Nanik; Subhan, Putri Bulkis (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
This study aims to describe a political phenomenon in the Moskona Teluk Bintuni indigenous community, by covering the objective task as the focus of the analysis. First, the Bakar Babi (Pig Burning) Ritual in the Moskona Tribe Culture. Second, the bakar babi as a Political Symbol in Moskona Tribe Solidarity in the Political Realm, and Third, Social Capitalization in the Tribal Chief's Victory in the 2019 Legislative Election in Teluk Bintuni. This study used social capital theory to analyze, describe and direct this research to find the meaning of the truth about the Bakar Babi ritual and its relationship in the legislative election arena. While the qualitative research approach with descriptive research type, and data collection were carried out through interviews, observations and in-depth and relevant literature studies. From the three research objectives, it was found that the Bakar babi ritual is part of the culture and mechanism of life in the social life of the Moskona tribe, and until now it continues to be preserved. More profoundly, the Bakar Babi ritual has become a political symbol constructed as a cultural ritual of victory and maintaining social solidarity, which is nothing more than a node of political power for the victorious elite in political contests. The Moskona people believe that the tribe is the source of truth and goodness, therefore, the process of capitalizing on social capital is very effective in winning in the political arena.